When ethnicity is stronger than religion: A look into Dayaks and Madurese Conflicts in Kalimantan, Indonesia - Achmad Ubaedillah (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2022)
Although there are some incoming ethnicities in Borneo such as Malays, Chinese, Buginese, Javanese and Madurese, only with Madurese that the indigenous Dayaks conflicted with, despite being in the same faith that is Islam. This paper discusses ethnic conflict that occurred in Sambas District, West Borneo in 1999 between the indigenous Dayaks and the immigrant Madurese. Using Schmidt and Schroder’s (2001) framework of violent acts and social ramifications, this article looks into contributing factors of this conflict and how these factors interrelated. The study finds that Sambas outbreak was driven by an external factor such as central government’s transmigration policy that impacted on Dayak traditional lands and forests and economic deprivation. Additionally, there was also accumulating historical clash between Dayaks and Madurese, fueling the hatred toward the transmigrating group. An important finding to note is that Dayak Muslims and Malays also shared religious belief as do Dayak Muslims and Madurese, but they did not conflict with each other. This study suggests that ethnicity needs to be considered when dealing with conflicts in local areas, and state government should take into account the local political and economic constellation before enforcing transmigration policy.